0.09-0.01(x+1)=-0.03(4-x)

Simplify each term.

Apply the distributive property.

0.09-0.01x-0.01⋅1=-0.03(4-x)

Multiply -0.01 by 1.

0.09-0.01x-0.01=-0.03(4-x)

0.09-0.01x-0.01=-0.03(4-x)

Subtract 0.01 from 0.09.

-0.01x+0.08=-0.03(4-x)

-0.01x+0.08=-0.03(4-x)

Apply the distributive property.

-0.01x+0.08=-0.03⋅4-0.03(-x)

Multiply.

Multiply -0.03 by 4.

-0.01x+0.08=-0.12-0.03(-x)

Multiply -1 by -0.03.

-0.01x+0.08=-0.12+0.03x

-0.01x+0.08=-0.12+0.03x

-0.01x+0.08=-0.12+0.03x

Subtract 0.03x from both sides of the equation.

-0.01x+0.08-0.03x=-0.12

Subtract 0.03x from -0.01x.

-0.04x+0.08=-0.12

-0.04x+0.08=-0.12

Subtract 0.08 from both sides of the equation.

-0.04x=-0.12-0.08

Subtract 0.08 from -0.12.

-0.04x=-0.2

-0.04x=-0.2

Divide each term in -0.04x=-0.2 by -0.04.

-0.04x-0.04=-0.2-0.04

Cancel the common factor of -0.04.

x=-0.2-0.04

Divide -0.2 by -0.04.

x=5

x=5

Solve for x 0.09-0.01(x+1)=-0.03(4-x)